Policy of Decrease Customer’s No-show at Restaurants - Li, Kuo-Pin; Chen, Shieh-Liang; Chiu, Wen-Hong; Lu, Wen-Cheng (International Journal of Engineering and Technology, 2019)
No-show reduction at restaurants can not only mitigate losses incurred when customers fail to honor a booking but also affect consumers’ reservation behaviors. This study analyzed the ability of restaurant booking policies to reduce no-shows as well as the negative impacts. We herewith to summarize the results of the interview and suggest four reduce No-Show policies for restaurants, they are Re-offering seats, Overbooking, Partial reservations, and No-show penalties. These four methods are also the most common reduce No-Show policies for restaurants. A survey was conducted to understand the booking policies of the Taiwanese restaurant industry. The findings indicated that each sector of the restaurant industry possesses unique characteristics. This study shows that restaurant differentiation is important in setting booking policies. Reservation no-shows cause problems to wasted capacity and result in restaurants’ losses. Our goal is to solve the wasted capacity and mitigation no-show loss, and to offer recommendations on what restaurants should do. Study was found that the restaurant operators generally believed that it was effective to have no-show penalty. Only each restaurant still has its own operating factors that affect its execution ability; the study also found that restaurants of different sizes may have variant reservation policies.  So, The Restaurants can decrease No-show by 1.Re-offering seats, 2.No-show penalties, or 3.Overbooking and Partial reservations are interactions impact degree of customer’s no-show.